The Execution of Third Party Mortgage Guarantees in Rural Bank Credit Agreements - Rizka Rian Ananda; Umar Ma'ruf (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2021)
This study aims to determine the execution of mortgage guarantees on bank credit agreements belonging to third parties at Rural Banks. The Method approach in this research is empirical juridical with primary and secondary research data taken by interview and literature review. Data analysis method using qualitative analysis. The results of the study indicate that the execution of mortgage rights belonging to third parties in BPR X is in accordance with the rules in Article 1 and Article 6 of Act No. 4 of 1996 concerning Mortgage Rights and carried out by the KPKNL. The execution of mortgage rights belonging to third parties in the BPR credit agreement in the event of a fight must be able to show proof of ownership but the execution process must still be carried out. Legal remedies for third parties as owners of land rights that are used as objects of mortgage rights are that they can file a lawsuit or derden verzet to the District Court, although this method cannot in principle suspend execution (Article 207 paragraph (3) HIR and 227 RBg) especially if from the start the third party agrees that the land is used as collateral for mortgage rights.